IS THE PRESENT ORGANIZATIONAL CULTURE OF HUNGARIAN COMPANIES AFFECTED BY THEIR PAST STATE OWNERSHIP (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
This study examines empirically how culturally rooted behavior forms can be detected in Hungarian organizations that were state-owned before the transition. A hypothesis is established and tested through the statistical analysis of a questionnaire-based survey conducted at the Faculty of Business and Economics, University of Pecs, Hungary. The original hypothesis is confirmed by the results of the analysis.